Cardiovascular consequence of reclining vs. sitting beach-chair body position for induction of anesthesia - Larsen, Søren L.; Lyngeraa, Tobias S.; Maschmann, Christian P.; Van Lieshout, Johannes J.; Pott, Frank C. (Frontiers in Physiology, 2014)
The sitting beach-chair position is regularly used for shoulder surgery and anesthesia may be induced in that position. We tested the hypothesis that the cardiovascular challenge induced by induction of anesthesia is attenuated if the patient is placed in a reclining beach-chair position. Anesthesia was induced with propofol in the sitting beach-chair (n=15) or with the beach-chair tilted backwards to a reclining beach-chair position (n=15). The last group was stepwise tilted to the sitting beach-chair position prior to surgery. Hypotension was treated with ephedrine. Continuous hemodynamic variables were recorded by photoplethysmography and frontal cerebral oxygenation (ScO2) by near infrared spectroscopy. Significant differences were only observed immediately after the induction when patients induced in a reclining beach-chair position had higher mean arterial pressure (MAP) (35±12 vs. 45±15 % reduction from baseline, p=0.04) and ScO2 (7±6 vs. 1±8 % increase from baseline, p=0.02) and received less ephedrine (mean: 4 vs. 13 mg, p=0.048). The higher blood pressure and lower need of vasopressor following induction of anesthesia in the reclining compared to the sitting beach-chair position indicate more stable hemodynamics with the clinical implication that anesthesia should not be induced with the patient in the sitting position.